Exosome-Based Delivery of Natural Products in Cancer Therapy - Song, Hang; Liu, Bin; Dong, Bin; Xu, Jing; Zhou, Hui; Na, Sha; Liu, Yanyan; Pan, Yunxia; Chen, Fengyuan; Li, Lu; Wang, Jinghui (Frontiers in Cell and Developmental Biology, 2021)
A rapidly growing research evidence has begun to shed light on the potential application of exosome, which modulates intercellular communications. As donor cell released vesicles, exosomes could play roles as a regulator of cellular behaviors in up-taken cells, as well as a delivery carrier of drugs for targeted cells. Natural product is an invaluable drug resources and it is used widely as therapeutic agents in cancers. This review summarizes the most recent advances in exosomes as natural product delivery carriers in cancer therapy from the following aspects: composition of exosomes, biogenesis of exosomes, and its functions in cancers. The main focus is the advantages and applications of exosomes for drug delivery in cancer therapy. This review also summarizes the isolation and application of exosomes as delivery carriers of natural products in cancer therapy. The recent progress and challenges of using exosomes as drug delivery vehicles for five representative anti-cancer natural products including paclitaxel, curcumin, doxorubicin, celastrol, and β-Elemene. Based on the discussion on the current knowledge about exosomes as delivery vehicles for drugs and natural compounds to the targeted site, this review delineates the landscape of the recent research, challenges, trends and prospects in exosomes as delivery vehicles for drugs and natural compounds for cancer treatment.